Analysis of shaft movement using FEM model considering inertia effect of club head - Matsumoto, K.; Tsujiuchi, N.; Koizumi, T.; Ito, A.; Ueda, M.; Okazaki, K. (Procedia Engineering, 2015)
Previous studies simulating shaft movement during a golf swing demonstrate shaft movement using a finite element method (FEM) model with the club head modelled as a concentrated mass. The objectives of this study are to simulate shaft movement while taking into account the inertia effect of the club head. A head was attached to a FEM model of the shaft as a simplified rigid model. We also compared the experimental results and simulation results of the shaft behavior. The simulated results corresponded to the experimental results and we therefore concluded that the inertia force of the club head causes deflection during the swing and torque of inertia angle of the twist during the swing.